1986
DOI: 10.1136/bmj.293.6549.735
|View full text |Cite
|
Sign up to set email alerts
|

Detection of patients with high alcohol intake by general practitioners.

Abstract: General practitioners have the potential to treat patients with alcohol problems effectively. Despite the medical implications of excessive alcohol intake, it appears that general practitioners are not sufficiently aware of the drinking habits of their patients. The aim of the study was to investigate the accuracy of 56 randomly chosen general practitioners in detecting which of their patients had a high alcohol intake. Altogether, 2081 patients were recruited in general practitioners' waiting rooms, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(49 citation statements)
references
References 0 publications
3
46
0
Order By: Relevance
“…We speculate that these low rates of referral may be due to the combination of low rates of detection, low rates of willingness to treat these problems, low awareness of service availability and intake procedures and finally low motivation on the part of the patients to enter a stigmatized treatment service. The low estimated detection rate is consistent with other studies, which find that GPs do not identify a majority of their at-risk patients [11,12]. It does not suggest that screening rates have improved much in response to educational and training initiatives.…”
Section: Discussionsupporting
confidence: 90%
“…We speculate that these low rates of referral may be due to the combination of low rates of detection, low rates of willingness to treat these problems, low awareness of service availability and intake procedures and finally low motivation on the part of the patients to enter a stigmatized treatment service. The low estimated detection rate is consistent with other studies, which find that GPs do not identify a majority of their at-risk patients [11,12]. It does not suggest that screening rates have improved much in response to educational and training initiatives.…”
Section: Discussionsupporting
confidence: 90%
“…This difficulty of obtaining an accurate drinking history may lead to under diagnosis of hazardous alcohol use and related disorders. Indeed, it has been reported that as few as 28% of problem drinkers are recognized by their doctors [3].…”
Section: Introductionmentioning
confidence: 99%
“…Anderson also estimates that up to 98% of those who drink to excess are not being diagnosed by GPs. A study carried out by Reid et al [19] found that only 28% of self-proclaimed heavy drinkers were identified by their GP. It is apparent that these learning objectives are not being attained.…”
Section: Resultsmentioning
confidence: 98%